The Adjustment Process and the International Role of the Dollar - Blough, Roy (Journal of Finance, 1969)
Roy Blough, The Adjustment Process and the International Role of the Dollar, The Journal of Finance, Vol. 24, No. 2, Papers and Proceedings of the Twenty-Seventh Annual Meeting of the American Finance Association Chicago, Illinois December 28-30, 1968 (May, 1969), pp. 345-359